UNHCR's Influence on Turkish Government Policies towards the Refugees Crisis - Muttaqien, Audi Izzat; Muhammad, Ali (Global Strategis, 2023)
This research examines the influence of UNHCR as an international institution on Turkey in global refugee governance. The Syrian war was the cause of the large influx of refugees to Europe, Turkey, as a transit country, received many refugees who came before they were forwarded to third countries. Turkey has become the most significant country in responding refugee crisis, especially the Syrian refugee crisis. This study used a qualitative method of reading critically and then being analyzed for interpretation. The data was collected through library research. The author uses an international regime theory to explain the role of international institutions in influencing actors' behaviors. The results found that UNHCR, as an international institution, influences Turkey's behavior in dealing with refugee issues. UNHCR standards and refugee regulations affect Turkey to adjust and adopt policies in the field of education, temporary protection regulations, and policy standards for refugees with a certain sexual orientation. Even though UNHCR influences the Turkish government, referring to the theory as an international institution, UNHCR's role is not binding and intervening in Turkish policies. Hence, the policies adopted by the Turkish government are their own decisions because the policies also follow their goals. Keywords: International Institution, Policy Influence, Refugee, Turkey, UNHCR Penelitian ini mengkaji pengaruh UNHCR sebagai lembaga internasional terhadap Turki dalam tata kelola pengungsi global. Perang Suriah menjadi penyebab masuknya pengungsi dalam jumlah besar ke Eropa, Turki sebagai negara transit banyak menerima pengungsi yang datang sebelum diteruskan ke negara ketiga. Turki menjadi negara yang paling signifikan dalam merespon krisis pengungsi, khususnya krisis pengungsi Suriah. Penelitian ini menggunakan metode kualitatif membaca secara kritis kemudian dianalisis untuk interpretasi. Pengumpulan data dilakukan melalui studi kepustakaan. Penulis menggunakan teori rezim internasional untuk menjelaskan peran lembaga internasional dalam memengaruhi perilaku aktor. Hasil penelitian menemukan bahwa UNHCR sebagai lembaga internasional memengaruhi perilaku Turki dalam menangani isu pengungsi. Standar UNHCR dan peraturan pengungsi memengaruhi Turki untuk menyesuaikan dan mengadopsi kebijakan di bidang pendidikan, peraturan perlindungan sementara, dan standar kebijakan bagi pengungsi dengan orientasi seksual tertentu. Meskipun UNHCR memengaruhi Pemerintah Turki, mengacu pada teori sebagai lembaga internasional, peran UNHCR tidak mengikat dan mengintervensi kebijakan Turki. Oleh karena itu, kebijakan yang diambil oleh Pemerintah Turki adalah keputusan mereka sendiri karena kebijakan tersebut juga sesuai tujuan mereka. Kata-kata kunci: Institusi Internasional, Pengaruh Kebijakan, Pengungsi, Turki, UNHCR